Roles and Experiences of Healthcare Professionals in Caring For Persons with Cleft Lip and/or Palate at the Komfo Anokye Teaching Hospital, Kumasi-Ghana: Healthcare Professionals’ Roles in Cleft Care (Journal of Science and Technology, 2025)
The specific roles and experiences of healthcare professionals in caring for CL/P patients are investigated. A case study of the qualitative approach was used. The study setting was the Multidisciplinary Cleft Clinic at the Komfo Anokye Teaching Hospital (KATH). Eleven healthcare professionals participated in the study. The study employed in-depth interviews to obtain rich, lived experiences of the participants. Themes identified included multi-disciplinary approach to care, patient and family centered care, collaboration with external organizations, longevity and experience in the field, patient reception and psychological support, financial and procedural counseling, building supportive relationship, geographic distribution and relocation of parents, psychological impact of CL/P on parents, emotional transformation, societal stigma and misconception, financial strain, social and emotional implications. The analysis of the roles and experiences of healthcare professionals highlights the importance of a comprehensive approach involving surgeons, paediatricians, orthodontists, nurses, nutritionists, social workers and representatives from the Ghana Cleft Foundation and Smile Train. This multi-disciplinary strategy addresses not only surgical aspects but also pre- and post-surgical care, genetics research, nutritional support, orthodontic care, speech therapy, and psychological assistance. The study confirms that holistic treatment and care for CL/P go beyond general medical care. This study emphasises the need for a multidisciplinary approach to CL/P care, accentuating that treatment extends beyond surgery to include nutrition, speech therapy, psychological support, financial assistance, and social integration. Establishing consistent collaborations among healthcare professionals, government, and philanthropic organisations is crucial in ensuring access to comprehensive cleft care.